2016
DOI: 10.1186/s12885-016-2166-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer literacy among higher secondary students: results from a cross-sectional study in Western Nepal

Abstract: BackgroundBeing the most common cancer among women worldwide, it is vital to be well-aware of breast cancer risk factors, symptoms and curability. However, few studies have reported breast cancer literacy in students using a validated instrument.MethodsA cross-sectional study was conducted among students of grades 11 and 12 from eleven higher secondary schools, one selected randomly from each ilaka of Parbat district. Questionnaire with modified Comprehensive Breast Cancer Knowledge Test was self-administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 21 publications
(23 reference statements)
3
25
3
Order By: Relevance
“…Breast cancer is one of the most common cancers and the fifth leading cause of cancer-related deaths among women worldwide [1]. The clinical diagnostic methods for breast cancer include physical examinations, mammography and histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is one of the most common cancers and the fifth leading cause of cancer-related deaths among women worldwide [1]. The clinical diagnostic methods for breast cancer include physical examinations, mammography and histopathology.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Bhandari PM et al, showed that the overall knowledge level of breast self-examination among Nepalese women was low to moderate. 29 In remote areas of Nepal women's disbelief that events are governed by fate and no one could change the course of the events. These kind fatalistic attitudes are responsible for late detection of breast cancer in Nepal.…”
Section: Breast Cancer Screening In Nepalmentioning
confidence: 99%
“…Some limited studies in Nepal have shown that the awareness level about risk factors and early detection measures of breast cancer among Nepalese women such as clinical breast examination (CBE) and breast selfexamination (BSE) was low. 9,10,29 Furthermore a crosssectional study conducted in western Nepal among higher secondary students found that the students have a poor knowledge on many breast cancer risk factors, symptoms and curability and most of them had misleading information about age, early menarche and delayed menopause as the risk factor. 29 In Nepal cancer prevention, education, and access to cancer screening tests as well as cancer treatment are inadequate.…”
Section: Challenges In Breast Cancer Prevention and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have repeatedly demonstrated that irrespective of their socio-economic and educational backgrounds, Nepalese women had poor knowledge of the risk factors of breast cancer (8,9,50). Although age, education, household income and family history of breast cancer are reported to be significantly associated with awareness level, a study on breast cancer literacy among higher secondary students demonstrated that students had poor knowledge on breast cancer risk factors, symptoms and curability (50). Furthermore, most of the students lacked awareness of age, early menarche, delayed menopause and use of the oral contraceptive pill as being the risk factors for breast cancer.…”
Section: Breast Cancer Awareness and Future Directionsmentioning
confidence: 99%